Thyrotropin Receptor Epitope and Human Leukocyte Antigen in Graves’ Disease - Inaba, Hidefumi; De Groot, Leslie J.; Akamizu, Takashi (Frontiers in Endocrinology, 2016)
Graves’ disease (GD) is an organ-specific autoimmune disease, and Thyrotropin (TSH) receptor (TSHR) is a major autoantigen in this condition. Since the extracellular domain of human TSHR (TSHR-ECD) is shed into the circulation, TSHR-ECD is a preferentially immunogenic portion of TSHR. Both genetic factors and environmental factors contribute to development of GD. Inheritance of HLA genes, especially HLA-DR3, is associated with GD. TSHR-ECD protein is endocytosed into antigen presenting cells (APCs), and processed to TSHR-ECD peptides. These peptide epitopes bind to HLA-class II molecules, and subsequently the complex of HLA-class II and TSHR-ECD epitope is presented to CD4+ T-cells. The activated CD4+ T-cells secrete cytokines/chemokines that stimulate B-cells to produce TSAb, and in turn hyperthyroidism occurs. Numerous studies have been done to identify T- and B-cell epitopes in TSHR-ECD, including 1) in silico, 2) in vitro, 3) in vivo, and 4) clinical experiments. Murine models of GD and HLA-transgenic mice have played a pivotal role in elucidating the immunological mechanisms. To date, linear or conformational epitopes of TSHR-ECD as well as the molecular structure of the epitope binding groove in HLA-DR, were reported to be related to the pathogenesis in GD. Dysfunction of central tolerance in the thymus, or in peripheral tolerance such as regulatory T-cells, could allow development of GD. Novel treatments using TSHR antagonists or mutated TSHR peptides have been reported to be effective. We review and update the role of immunogenic TSHR epitopes and HLA in GD, and offer perspectives on TSHR epitope specific treatments.